ISOLASI DAN IDENTIFIKASI BAKTERI PEREDUKSI SULFAT DARI KAWASAN PLTP KAMOJANG JAWA BARAT - Dwi Suhartanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2004)
Tlte isolation and identification of sulfat reducing bacteria (SRB) had been performed at Kamojang Geothermal Power Plant. Isolation and identification of sulfat reducer bcrcteria from the soil and corroded steel  bolt obtained from the area of Kamojang Geothermal  power plant.  Four (4)  spesies  of bacterias were obtained from the soil among  them were Desulfotomaculum  spl, Desulfutomaculum  sp2,  Desulfotomaculum sp3, Desulfomonas  pigra,  and  ones  (l)  spesies from coruoded  steel  bolt  Desulfovibrio sp.